2010
DOI: 10.1136/emj.2009.076414
|View full text |Cite
|
Sign up to set email alerts
|

Major trauma CT scanning: the experience of a regional trauma centre in the UK

Abstract: Our major trauma CT protocol, based on mechanism of injury, resulted in substantial changes in clinical management in a small number of patients without any increase in adverse events. However, it is not a substitute for clinical acumen in the initial assessment of trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
2
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 18 publications
4
61
2
3
Order By: Relevance
“…Despite this being a significant proportion of all patients examined, the present findings are similar to those previously published in the literature. 2,19,20 In the present study, 93% of patients had fewer body areas injured than clinically suspected. Although this may not be entirely unexpected, the fact that less than 2% of patients had injuries to all four body areas and that the "no injuries" or "injury to one body area" groups were the largest, does suggest that there is an overtendency to clinically categorise patients as being polytrauma victims and investigate them with WBCT.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Despite this being a significant proportion of all patients examined, the present findings are similar to those previously published in the literature. 2,19,20 In the present study, 93% of patients had fewer body areas injured than clinically suspected. Although this may not be entirely unexpected, the fact that less than 2% of patients had injuries to all four body areas and that the "no injuries" or "injury to one body area" groups were the largest, does suggest that there is an overtendency to clinically categorise patients as being polytrauma victims and investigate them with WBCT.…”
Section: Discussionmentioning
confidence: 41%
“…injuries, detecting clinically significant injuries that would have been missed pre-protocol, and faster time to definitive diagnoses are some of the benefits reported as a result of mandatory WBCT trauma protocol 21e23 ; however, introducing a mandatory WBCT protocol has been associated with increased numbers of negative examinations when compared to pre-protocol WBCT imaging. 20 Asha et al 10 found that a mandatory WBCT protocol led to a significant increase in radiation exposure. Hsiao et al 9 concluded that a prediction model for using WBCT did not significantly alter clinical accuracy and advocated using a thorough clinical assessment by the emergency physician as the most appropriate method to decide on the indication for WBCT.…”
Section: Discussionmentioning
confidence: 99%
“…4,8Y12 The alternative to early WBCT is a selective approach to imaging, often with conventional radiographs of the spine, and selective CT scanning based on one or more of the history of the injury, the physical examination, and other investigation results. The two approachesVWBCT and selective CTVdiffer in a number of potential ways: WBCT may give more rapid diagnosis and therefore earlier treatment, better outcomes, and shorter hospital stays, 13,14 and it may lead to fewer missed injuries 13,15,16 and result in fewer overall scans; 10,11,14 in contrast, it may delay time-critical interventions and it may expose patients to greater radiation and may be more expensive. 17Y20 The use of WBCT in trauma care is therefore at the intersection of two countervailing trends: one toward increased imaging to more efficiently diagnose and manage injuries; the other to minimize unnecessary and harmful radiation exposure that may pose future cancer risks or teratogenicity to an unborn child.…”
mentioning
confidence: 99%
“…During the study period, 60 major trauma patients were admitted to our centre, 36 of which met inclusion criteria (78% male with median (IQR) age 38 (27-68) years) with a median (IQR) ISS of 25 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and ICU stay of 5 (2-10) days. Injuries were predominantly due to blunt trauma (Figure 1).…”
Section: Resultsmentioning
confidence: 99%